Indústria têxtil cearense: reverticalização de processos e seus impactos sobre a qualidade e a produtividade - Lezeck, Hendrick (2007)
This work aims to verify the impacts that the reversing process in the results of quality and productivity produced in textile companies in Ceará which adopted this strategy. After analyzing the value chains, many companies that at first outsourced are now rethinking their decisions and when needed taking an inverse approach, that is, not outsourcing their activities any more. That is why it is important to understand what are the main factors that lead to this process. The research related to the outcome is of descriptive and exploring nature; regarding the approach to the problem, it is of quality concerning. Based on bibliographic research that subsidized the referential theory proceeded further investigation giving support to the empirical analyses. Semi-structured Questioner and interviews were carried out with executives managers and operatives in three textile companies of great capacity in Ceará, based in deliberate exemplification. The results show that the strategic decisions of the reversing process has been motivated by the commitment to the quality of products and procedures, targeting mainly the best quality service to the clients. This derived from several problems pointed out by companies that by outsourcing operate.